Androgen deficiency and metabolic syndrome in men - Winter, Ashley G.; Zhao, Fujun; Lee, Richard K. (Translational Andrology and Urology, 2014)
Metabolic syndrome (MetS) is a growing health concern worldwide. Initially a point of interest in cardiovascular events, the cluster of HTN, obesity, dyslipidemia, and insulin resistance known as MetS has become associated with a variety of other disease processes, including androgen deficiency and late-onset hypogonadism (LOH). Men with MetS are at a higher risk of developing androgen deficiency, and routine screening of testosterone (T) is advised in this population. The pathophysiology of androgen deficiency in MetS is multifactorial, and consists of inflammatory, enzymatic, and endocrine derangements. Many options for the concomitant treatment of both disorders exist. Direct treatment of MetS, whether by diet, exercise, or surgery, may improve T levels. Conversely, testosterone replacement therapy (TRT) has been shown to improve MetS parameters in multiple randomized controlled trials (RTCs).